Pengaruh E-Commerce dan Penggunaan Sistem Informasi Akuntansi dalam Pengambilan Keputusan untuk Berwirausaha Di Sektor Agro And Marine Industry (Studi Pada Mahasiswa Akuntansi Universitas Teuku Umar) - Azmir Gani; Ika Rahmadani; Sari Maulida Vonna; Linda Rahmazaniati; Rina Maulina (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2022)
This research aims to examine the influence of e-commerce and the use of accounting information systems in decision making for entrepreneurship in the agro and marine industry sector in accounting students of Teuku Umar University. The population in this study is all active students of the Accounting Study Program class of 2017 and 2018, Faculty of Economics, Teuku Umar University who have taken courses in entrepreneurship and accounting information systems. The data analysis method used in this study is multiple linear regression analysis using SPSS and Microsoft Excel programs. Based on the results of research it is known that partially, e-commerce has a significant and positive influence on entrepreneurship decision making. The use of accounting information systems affects decision making. While simultaneously e-commerce and the use of accounting information systems have a significant effect on decision making for entrepreneurship